Development of mechanically robust self-cleaning coatings for large structure protection - Kumar, Divya (2016)
With increasing focus on sustainable and environment friendly solutions for day-to-day applications, several new technologies are being developed or existing ones are being improved upon. Self-cleaning coatings and surfaces is one such area which is getting constant attention from today’s scientific and industrial community. These coatings can effectively reduce cleaning and maintenance requirements and also prevent unwarranted damage and failure of machines or structures due to surface contamination. There are several ways to introduce self-cleaning functionality to a surface viz. photocatalytic, superhydrophilic or superhydrophobic methods. This project mainly concentrates on the development of different superhydrophobic coatings that can be applied on a surface to make it self-cleaning. A surface that is superhydrophobic possesses a water contact angle (CA) > 150° and low sliding angles (SA). The main principle behind superhydrophobicity is that the surfaces with this functionality have high resistance to wetting. Typically the formulation of these coatings contains use of soft polymer blocks and various organic surface modifiers. This in turn compromises the mechanical durability of the coatings when exposed to harsh environments. The main objective of this project is to develop self-cleaning coatings for large outdoor structures like wind turbine blades and aircraft wings with enhanced mechanical properties. The project aims to achieve this through understanding the main factors affecting the key functionalities of abrasion and erosion resistant self-cleaning coatings. Further, there are no standardized test methods to evaluate the effectiveness of such coatings. This project also aims at developing basic tests to evaluate the performance of various self-cleaning systems. This work includes formulation, synthesis, characterization and mechanical testing of three different coating systems. The first system was based on a sol-gel formulation for producing an organic-inorganic matrix using a silane, tetraethylorthosilicate (TEOS) and an epoxy silane, glycidoxypropyltriethoxylsilane (Glymo). The hydrophobic functionality was introduced by addition of low energy molecules like fluoroalkylsilanes and particulate silica fillers. Though this system yielded coatings that exhibited a combination of contact angle > 150° and sliding angle < 5°, the mechanical durability, erosion and abrasion resistance were not extremely high. In order to further improve the mechanical properties of this system, amine cured Glymo was used. This modification produced coatings that showed improved mechanical resistance compared to the previous composition. The second system also involves TEOS as a precursor along with the viscoelastic polymer polydimethylsiloxane (PDMS) acting as the hydrophobic agent. The PDMS due to its Si-O-Si network also contributed to the formation of the matrix along with TEOS. At a particular composition, these coatings exhibited dynamic hydrophobicity (i.e.) sliding of water droplets at angles < 10° even though the contact angle of these coatings were not > 150°. These coatings also proved to possess satisfactory mechanical properties and resistance to abrasion and erosion which is attributed mainly to the presence of the viscoelastic polymer PDMS. On adding particulate silica fillers (10-20 nm) to the coating, they moved from being dynamically hydrophobic to superhydrophobic. The final coating system studied was based on the thermoplastic fluoropolymer polyvinylidene fluoride (PVDF). PVDF is hydrophobic by itself but modification with particulate fillers produced coatings that were extremely superhydrophobic. Previous literature indicates that most PVDF based coatings do not have good adhesion with the substrates. This was addressed by pre-treating the substrates with (3 Aminopropyl)triethoxysilane (APTES) which functionalizes the surface, improving coating adhesion significantly. Increasing filler concentration improves the hardness of the coatings though the Young’s modulus decreases. The resistance to abrasive wear and erosion is seen to decrease with increase in filler concentration. Superhydrophobic functionalities of the coatings are retained after abrasion and erosion. A test was developed to measure the self-cleaning performance of the coatings. The principle of spectrophotometry was used to establish the extent of self-cleaning performance shown by various coatings. An artificial dirt mixture prepared in the lab was used to test the self-cleaning performance. In order to establish which factors influence the self-cleaning performance of the coatings, the effect of various physical properties including CA, SA, roughness, interfacial surface energy, the work of adhesion and retention force were studied. In conclusion, three different coating compositions with hydrophobic/superhydrophobic properties were developed. The various coating compositions were studied in detail for their mechanical properties and the effect of abrasive and erosive wear. Correlation between the physical parameters and self-cleaning performance of the coatings were established. A new method to systematically measure the self-cleaning performance of coatings is described and tested. From the various systems studied, it is seen that a balance between mechanical performance and hydrophobicity can be achieved by effective optimization of surface and chemical modification. This study opens a new avenue which shows that superhydrophobicity is not always necessary to achieve effective self-cleaning properties.